Pertentangan Kelas Sosial dalam Naskah Drama Kapai-Kapai Karya Arifin C. Noer - Husnul Fikri; Hasanuddin WS Hasanuddin WS (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to reveal the forms of social class conflict, the factors that cause social class conflict, and the impact of social class conflict in the play Kapai-Kapai by Arifin C. Noer. This type of research is descriptive qualitative research. The main data source in this research is Kapai-Kapai drama script by Arifin C. Noer. The research data collection techniques are; (1) Reading and understanding the play Kapai-Kapai by Arifin C. Noer; (2) Literature review in order to obtain an understanding of the problem to be studied; and (3) Inventory of data related to social class opposition depicted in the play Kapai-Kapai by Arifin C. Noer. The data validation technique used is triangulation technique. The forms of social class opposition from the play Kapai-Kapai by Arifin C. Noer: includes: 15 objective data, 27 subjective data. In addition, there are factors that cause social class conflict in the Kapai-Kapai drama script by Arifin C. Noer, such as: community relations, human needs, negotiation, intercultural misunderstanding, and conflict transformation. The impacts of the social class conflict are: an increased sense of group solidarity, the destruction of group unity, changes in individual personality (4) the destruction of existing values and norms, and the loss of property (material) and people.